Effect of supplementing graded levels of organic and inorganic chromium on the performance and anti-oxidant status in commercial broilers - reddy, eevuri tirupathi (Indian Journal of Animal Nutrition, 2018)
The present experiment was conducted to study the effects of inclusion of graded levels of organic and inorganic chromium (Cr) at 0, 300, 600, 900, 1200 and 1500 Âµg/kg of diet, separately in a 5 x 2 factorial manner on the performance and anti-oxidant status of broilers. A total of 440 day-old commercial broiler male chicks were divided into 11 dietary treatments with 8 replicates (5 broilers in each replicate) and fed test diets ad-lib from day-one to 42 days of age (pre-starter 0-14 d, starter 15-28 d and finisher 29-42 d). Feed intake (FI) was more (P